PENGEMBANGAN MEDIA PEMBELAJARAN RAGAM BAHASA PADA MATA KULIAH PENGEMBANGAN KEPRIBADIAN (MPK) BAHASA INDONESIA MENGGUNAKAN SPARKOL VIDEO SCRIBE UNTUK MAHASISWA SEMESTER I STIE APRIN PALEMBANG - Serli Lestari (Sekolah Tinggi Ilmu Ekonomi (STIE) Aprin, 2020)
This study aims to (1) find out the need for a Variety of Language Learning Media in the Indonesian Personality Development Subject (MPK) using Sparkol Video Scribe according to students and lecturers, (2) design media based on the analysis of student and lecturer needs, (3) describe the results of self an evaluation of the paper based development media, (4) describing the results of expert validation on the development media, (5) knowing the practicality of the media based on one-to-one and small group trials, and (6) knowing the potential effects of instructional media on student learning outcomes. This research and development method modifies and collaborates on the development theories of Kirschner, Valcke, and Sluiijsmans (in Akker, et al. 1999: 89) and Tessmer (1998: 35). This development media was prepared based on the results of the analysis of the needs of students of STIE APRIN Palembang This media framework consists of a homepage menu, instructions, objectives, material, training, evaluation, biodata. This media has been tested through validation by three experts covering aspects of eligibility: material, language, and media. Based on the validation of the three experts, the conclusion is that the media is valid and worth testing with revisions according to the comments and suggestions of the experts. Based on the results of one-to-one trials and small media groups practically used by students. Based on the results of field trials through pretest and posttest, the average value of the variety of MPK languages ​​in Indonesian students increased from 63.26 to 84.56 (difference 21).